5-HT7 receptors as modulators of neuronal excitability, synaptic transmission and plasticity: physiological role and possible implications in autism spectrum disorders - Ciranna, Lucia; Catania, Maria Vincenza (Frontiers in Cellular Neuroscience, 2014)
Serotonin type 7 receptors (5-HT7) are expressed in several brain areas, regulate brain development, synaptic transmission and plasticity, and therefore are involved in various brain functions such as learning and memory. A number of studies suggest that 5-HT7 receptors could be potential pharmacotherapeutic target for cognitive disorders. Several abnormalities of serotonergic system have been described in patients with autism spectrum disorder (ASD), including abnormal activity of 5-HT transporter, altered blood and brain 5-HT levels, reduced 5-HT synthesis and altered expression of 5-HT receptors in the brain. A specific role for 5-HT7 receptors in ASD has not yet been demonstrated but some evidence implicates their possible involvement. We have recently shown that 5-HT7 receptor activation rescues hippocampal synaptic plasticity in a mouse model of Fragile X Syndrome, a monogenic cause of autism. Several other studies have shown that 5-HT7 receptors modulate behavioral flexibility, exploratory behavior, mood disorders and epilepsy, which include core and co-morbid symptoms of ASD. These findings further suggest an involvement of 5-HT7 receptors in ASD. Here, we review the physiological roles of 5-HT7 receptors and their implications in Fragile X Syndrome and other ASD.